2017
DOI: 10.1371/journal.pone.0185979
|View full text |Cite|
|
Sign up to set email alerts
|

Interoception and sexual response in women with low sexual desire

Abstract: Sexual concordance is defined as the association between genital response and self-reported sexual arousal. Though one might predict a strong association between sexual concordance and awareness of other internal physiological sensations (termed interoception), past research on sexually healthy women has not found these different domains to be related. The aim of the present study was to test the association between interoception and sexual concordance in a clinical sample of women with Sexual Interest/Arousal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In women, more concordance is found in sexually functional signs ( Meston, 2006 ; Meston et al., 2010 ; Sarin et al., 2016 ). However, these are not conclusive results because some studies have not found this relation ( Brotto et al., 2016 ; Suschinsky et al., 2019 ; Velten & Brotto, 2017 ). Therefore, more research is necessary.…”
mentioning
confidence: 86%
“…In women, more concordance is found in sexually functional signs ( Meston, 2006 ; Meston et al., 2010 ; Sarin et al., 2016 ). However, these are not conclusive results because some studies have not found this relation ( Brotto et al., 2016 ; Suschinsky et al., 2019 ; Velten & Brotto, 2017 ). Therefore, more research is necessary.…”
mentioning
confidence: 86%
“…Recent research has explored the role of interoceptive awareness, defined as an individual's ability to recognize internal bodily states in women's sexual response (Velten & Brotto, ). These data indicate that women who are able to remain focused and challenge distractions were better able to experience sexual response, even when it was accompanied by negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may suggest that focusing on sensations in the genitals might induce a more localized focus of attention and might lead women to be less open to notice other physical sensations or thoughts. Future studies should aim to assess whether sexual mindfulness (Adam et al, 2015) or other potential mediators—such as interoceptive awareness (Velten & Brotto, 2017), negative expectancies, or rumination—might mediate the relationship between specific mindfulness exercises and sexual functioning in women (Stephenson, 2017).…”
Section: Discussionmentioning
confidence: 99%